2019
DOI: 10.1093/mnras/stz3580
|View full text |Cite
|
Sign up to set email alerts
|

Local RR Lyrae stars: native and alien

Abstract: Measurements of [Fe/H] and radial velocity are presented for 89 RR Lyrae (RRL) candidates within 6 kpc of the Sun. After the removal of two suspected non-RRL, these stars were added to an existing database, which yielded 464 RRL with [Fe/H] on a homogeneous scale. Using data from the Gaia satellite (Data Release 2), we calculated the positions and space velocities for this sample. These data confirm the existence of a thin-disc of RRL with [α/Fe]∼ solar. The majority of the halo RRL with large total energies h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 107 publications
(201 reference statements)
4
17
0
Order By: Relevance
“…Note that we could not perform this step for the RAVE metallicities because we found only one match between the RAVE and the HR+∆S RRLs, therefore the RAVE metallicities were not converted. We also note that, the fits for the Zinn et al (2020), Dambis et al (2013), Duffau et al (2014) and Sesar et al (2013) samples are close to the bisector, meaning that their metallicities aretaking account of the uncertainties -already in a scale very similar to our own. Additionally, we found that the metallicity scales of Liu et al (2020) and SEGUE-SSPP are different to ours.…”
Section: The Rrl Spectroscopic Catalogsupporting
confidence: 73%
“…Note that we could not perform this step for the RAVE metallicities because we found only one match between the RAVE and the HR+∆S RRLs, therefore the RAVE metallicities were not converted. We also note that, the fits for the Zinn et al (2020), Dambis et al (2013), Duffau et al (2014) and Sesar et al (2013) samples are close to the bisector, meaning that their metallicities aretaking account of the uncertainties -already in a scale very similar to our own. Additionally, we found that the metallicity scales of Liu et al (2020) and SEGUE-SSPP are different to ours.…”
Section: The Rrl Spectroscopic Catalogsupporting
confidence: 73%
“…The mean azimuthal velocity of the thin disc indicates that the motion of the Sun is around 232.5 km s −1 , which is consistent with the recent value derived from classical cepheids (Ablimit et al 2020). The faster azimuthal velocity and more metal-rich features of the thin disc compared to other components are consistent with previous studies (e.g., Preston 1959;Taam et al 1976;Layden 1995;Mateu & Vivas 2018;Marsakov et al 2019;Prudil et al 2020;Zinn et al 2020;Iorio & Belokurov 2021). There are relatively more thick disc stars in this work, and they do not rotate as fast as the thin disc stars.…”
Section: Properties Of Thin Disc Thick Disc and Halosupporting
confidence: 92%
“…The structure of the Milky Way thick disc have been characterized by RRLs as tracers (e.g., Layden 1995;Amrose & Mckay 2001). Zinn et al (2020) and Prudil et al (2020) combined RRL with available spectroscopy and Gaia DR2 astrometry to confirm the existence of metal-rich RRL stars with the orbital properties typical of the Galactic thin disc.…”
Section: Introductionmentioning
confidence: 99%
“…Hansen et al 2016) but they are also known to exist in the disc of the Galaxy (e.g. Layden 1995a; Liu et al 2013;Zinn et al 2020;Prudil et al 2020) and their formation mechanisms have long been source of puzzling (e.g. Taam et al 1976;Layden 1995b;Marsakov et al 2019).…”
Section: Formation Channels For Metal-rich Rr Lyrae Starsmentioning
confidence: 99%